Controls of the Lithospheric Thermal Field of an OceanContinent Subduction Zone: The Southern Central Andes - Rodriguez Piceda, Constanza (2022)
In an ocean-continent subduction zone, the assessment of the lithospheric thermal state is essential to determine the controls of the deformation within the upper plate and the dip angle of the subducting lithosphere. In this study, we evaluate the degree of inﬂuence of both the conﬁguration of the upper plate (i.e., thickness and composition of the rock units) and variations of the subduction angle on the lithospheric thermal ﬁeld of the southern Central Andes (29°–39°S). Here, the subduction angle increases from subhorizontal (5°) north of 33°S to steep (~30°) in the south. We derived the 3D temperature and heat ﬂow distribution of the lithosphere in the southern Central Andes considering conversion of S wave tomography to temperatures together with steady-state conductive thermal modeling. We found that the orogen is overall warmer than the forearc and the foreland and that the lithosphere of the northern part of the foreland appears colder than its southern counterpart. Sedimentary blanketing and the thickness of the radiogenic crust exert the main control on the shallow thermal ﬁeld (<50 km depth). Speciﬁc conditions are present where the oceanic slab is relatively shallow (<85 km depth) and the radiogenic crust is thin. This conﬁguration results in relatively colder temperatures compared to regions where the radiogenic crust is thick and the slab is steep. At depths >50 km, the temperatures of the overriding plate are mainly controlled by the mantle heat input and the subduction angle. The thermal ﬁeld of the upper plate likely preserves the ﬂat subduction angle and inﬂuences the spatial distribution of shortening.